'An Invested Interest in Language': Literary Practice in Secondary Classrooms. Issue 2 (3rd April 2019) - Duck, Paul
ABSTRACT: This essay draws on the work of Raymond Williams in identifying a shift from the attempt to have students engage with literary texts in personal terms to a concern, founded on theoretical innovation, that they should read at a more sophisticated level in order to discern the ideology of a given text. It argues that what Williams calls an 'expressivist' view of texts needs to be reconciled with, rather than displaced by, a 'formalist' conception of them. It finds that high-stakes examinations reward a focus on abstracted ideological concerns at the expense of responsiveness to language and form. Exploration of the work of a teacher whose career has spanned this shift identifies ways in which she has, in meeting the challenges of the classroom and of theory, sustained a professional practice that has informed and motivated her students' engagement with literary texts.